2021
DOI: 10.3390/biomedicines10010004
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Leptin Is Increased in Intensive Care Patients with COVID-19—An Investigation Performed in the PronMed-Cohort

Abstract: COVID-19 has shaken the world and intensive care units (ICU) have been challenged by numerous patients suffering from a previously unknown disease. Leptin is a polypeptide pleiotropic hormone, mainly expressed by adipocytes. It acts as a proinflammatory cytokine and is associated with several conditions, known to increase the risk of severe COVID-19. Very little is known about leptin in severe viral disorders. Plasma leptin was analyzed in 222 out of 229 patients with severe COVID-19 on admission to an ICU at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
2
18
0
1
Order By: Relevance
“…We and others have hypothesized that this chronic inflammatory state in individuals with obesity might exacerbate the immunopathology associated with SARS-CoV-2 infection in patients with obesity thereby rendering them susceptible to severe organ injury [ 11 , 12 ]. In line with this hypothesis, recent small studies from our group and others identified that plasma leptin was increased in COVID-19 patients admitted to the ICU [ 11 , 13 , 14 ]. Yet a decrease in Leptin in severe COVID-19 patients compared to mild and moderate COVID-19 was also found [ 15 ].…”
Section: Introductionsupporting
confidence: 63%
“…We and others have hypothesized that this chronic inflammatory state in individuals with obesity might exacerbate the immunopathology associated with SARS-CoV-2 infection in patients with obesity thereby rendering them susceptible to severe organ injury [ 11 , 12 ]. In line with this hypothesis, recent small studies from our group and others identified that plasma leptin was increased in COVID-19 patients admitted to the ICU [ 11 , 13 , 14 ]. Yet a decrease in Leptin in severe COVID-19 patients compared to mild and moderate COVID-19 was also found [ 15 ].…”
Section: Introductionsupporting
confidence: 63%
“…In the metaflammation of obesity, the inflamed adipose tissue is the driving force. The chronically slightly elevated proinflammatory cytokines (including leptin, which has been found to be elevated in COVID-19 patients [ 202 , 270 , 271 , 272 ]— Table 1 ) can cause SOCS1/3 induction [ 23 , 254 ], thus inhibiting the signaling of cytokines (such as interferons), leptin, and insulin [ 254 , 268 ]. “Resistance” arises, and that affects various organs, including parts of the immune system.…”
Section: Comprehensive Summary and Discussionmentioning
confidence: 99%
“…High levels of plasma leptin and adipokines are directly associated with the extent of obesity and have previously been shown to facilitate endothelial dysfunction (5,(20)(21)(22). Moreover, we and others reported before that plasma leptin levels are increased in critically ill COVID-19 patients (8,10,11). We therefore hypothesized that adipokines such as leptin may prime endothelial cells, thereby facilitating SARS-CoV-2 sensing and/or infection and driving the endothelial dysfunction which is characteristic of severe COVID-19.…”
Section: Leptin Does Not Facilitate Infection Nor Promote Activation ...mentioning
confidence: 87%
“…It is therefore hypothesized that this chronic inflammatory state might exacerbate the immune responses to SARS-CoV-2 infection in obese patients rendering them susceptible to severe disease (8,9). In line with this hypothesis, recent studies found plasma leptin to be increased in COVID-19 patients admitted to the intensive care (8,10,11).…”
Section: Introductionmentioning
confidence: 95%